COMMUNICATION FUNCTIONS OF THE TIMOR GONG IN NAPAN VILLAGE COMMUNITY - Agustinus Reno Renaldus Afoan El; Agustinus ABA Beda Ama; Melkior Melki Kian (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
The Timorese gong is a traditional musical instrument of the Napan people that functions as a means of communication in rituals and entertainment. This instrument consists of several parts, namely Tonu Mese, Ote and Kbola. This musical instrument is used by the community as their communication with the local community, ancestors and nature. The method used in this study is descriptive qualitative with an ethnographic approach, namely to discuss the culture and life of the local community. The Timorese Gong until now has functioned as a means of ritual communication where the Gong has a symbolic meaning, namely as a symbol of the strength, nature, identity and character of the community. Apart from being in the context of rituals, this musical instrument also serves to provide information to the local community, namely when there are traditional elders or traditional figures who have died. The Timor gong used as a communication for the Napan people is to provide certain information or messages related to what is about to happen, namely as a warning sign to the local community.Keywords: Gong Timor; Communication; Symbolic Meanin FUNGSI KOMUNIKASI GONG TIMOR PADA MASYARAKAT DESA NAPAN AbstrakGong Timor merupakan alat musik tradisi masyarakat Napan yang berfungsi sebagai sarana komunikasi dalam ritual maupun hiburan. Alat musik ini terdiri dari beberapa bagian yaitu Tonu Mese, Ote dan Kbola. Alat musik ini digunakan oleh masyarakat sebagai komunikasi mereka dengan masyarakat setempat, leluhur dan alam. Metode yang digunakan dalam penelitian ini ialah deskriptif kualitatif dengan pendekatan etnografi yaitu untuk membahas tentang kebudayaan dan kehidupan masyarakat setempat. Gong Timor hingga saat ini telah difungsikan sebagai sarana komunikasi ritual dimana Gong tersebut memiliki makna simbolik yaitu sebagai simbol keperkasaan, sifat, identitas dan karakter masyarakat. Selain dalam konteks ritual alat musik ini juga berfungsi untuk memberikan informasi kepada masyarakat setempat yaitu pada saat ada tua adat atau tokoh adat yang telah meninggal. Gong Timor yang digunakan sebagai komunikasi masyarakat Napan adalah untuk memberikan informasi atau pesan-pesan tertentu terkait dengan apa yang akan terjadi yaitu sebagai tanda peringatan pada masyarakat setempat.Kata Kunci: Gong Timor; Komunikasi; Makna Simbolik